The influence of some anthropometric parameters on the marathon results of the world athletics championships 2019 in Doha - Bekolli, L.; Rashiti, N.; Ramabaja, Q.; Heta, G. (Journal of Education, Health and Sport, 2023)
The research was conducted on a sample of 55 successful female marathoners who participated in ten of the most popular marathon races. The sample of subjects includes ten of the best marathoners positioned in every race held at the 2019 World Athletics Championships in Doha, Qatar. The purpose of the research is to assess the impact of body height, weight and age of marathon runners on the final result in the race. The collected data is processed by the basic descriptive parameters. The entities have the average weight of 60.81 kg, with the average height of 171.65 cm, at the average age of 32.92, with the achieved average result of 137.86 hours into the race. In the intercorrelation matrix, only a significant correlation coefficient (p<0.001) is obtained for height and body weight. From the regression analysis the influence of the predictor variables (height, weight and age) on the criterion variable – sig.=0,60 (the result of the marathon) is not confirmed, which provides only 36% (RO²=.366) of analysis in the common ground of variability. The remaining 64% of the analysis of the total variability of the criterion variable may be attributed to other anthropological characteristics, and mainly to functional characteristics of the anaerobic type.